Talent Management In Enhancing Corporate Competitiveness In The Era Of Industry 4.0: A Case Study Of Pt Nestlé Indonesia - Armando Monteiro; Darwati Susilastuti (PT. ALHAFI BERKAH INDONESIA, 2025)
This study aims to examine the role of talent management in enhancing corporate competitiveness in the era of Industry 4.0, using PT Nestlé Indonesia as a case study. A qualitative method was employed, utilizing a library research approach that analyzes various literature related to talent management and corporate competitiveness. Data were collected through a literature review involving books, journals, and relevant articles discussing the challenges and strategies of talent management in the context of technological change and digitalization. The findings indicate that effective talent management such as digital skills development, innovation in recruitment processes, and clear career planning plays a crucial role in improving corporate competitiveness. PT Nestlé Indonesia has implemented various talent management strategies to prepare its employees for the Industry 4.0 transformation. This study concludes that adaptive and future-oriented talent management is key to maintaining competitive advantage in the digital era.